The Implementation of Government Regulation of the Republic of Indonesia Number 19 of 2017 on Teachers in Elementary Schools in the Mentawai Islands Regency: Analyzing the Management Implementation of Government Regulation No. 19 of 2017 in Elementary School Teacher Management in Mentawai Islands Regency - Mega Rohaya; Desna Aromatica; Fatia Fatimah (Universitas Sumatera Barat, 2026)
This research analyzes the implementation of Government Regulation of the Republic of Indonesia Number 19 of 2017 concerning Teachers in Elementary Schools in Mentawai Islands Regency. The background of this research is the need to improve teacher professionalism as a key determinant of educational success. Although PP No. 19 of 2017 sets professional teacher qualification standards, the implementation of this regulation in Mentawai Islands Regency has not been carried out well. Many elementary school teachers in the area, especially in isolated regions, still have high school qualifications and do not meet the required S1 (bachelor's degree) standards, due to limited access and minimal qualified human resources. This condition is linked to potentially low student achievement. This study employs a qualitative method with an evaluative-exploratory approach to understand the meaning and dimensions of the experience of implementing government regulations by the actors involved. The analytical framework is based on George C. Edwards III's policy implementation model, which highlights four key factors: communication, resources, disposition (attitude), and bureaucratic structure. Data was collected through semi-structured interviews with the Head of the Education Office and their staff, local elementary school teachers, 5th and 6th-grade students, and parents, supplemented with secondary data from Dapodik. The research findings indicate that the implementation of PP No. 19 of 2017 faces various challenges. In terms of communication, policy information has been delivered to school principals and distributed to all elementary schools, but the overall understanding of the regulation among teachers remains uneven18. Regarding resources, the availability of S1 qualified teachers is still minimal; many teachers teach with high school qualifications due to urgent human resource needs, even though the teaching and learning process must continue. The disposition aspect shows that although teachers have a strong desire to meet S1 qualifications, they face obstacles such as poor internet access and high education costs for continuing their studies. The local government, through the Regent, has adopted a policy of relaxing qualifications due to teacher shortages, but still encourages teachers to pursue S1 degrees. From the bureaucratic structure perspective, coordination with the West Sumatra Provincial Government and the Regional Personnel Agency has been carried out to address teacher position formations. The conclusion of this research confirms that policy implementation is still not optimal due to challenges in teacher educational qualifications, human resource limitations, and the geographical conditions of remote areas. To enhance educational quality, practical recommendations include more intensive socialization, recruitment of S1 qualified contract teachers, professional training and development for teachers, improvement of infrastructure (especially internet access and educational facilities), and strengthening inter-agency coordination.